The perception of puerpers to the care provided by the nursing team regarding their puerperium (Research, Society and Development, 2021)
Introduction: The puerperal period constitutes a moment of fragility, demanding qualified and holistic care from health professionals, focused on the sociocultural and family context and on the evaluation of mother-child-family care. Objective: To analyze the perception of the puerpery woman to the care provided by a Family Health Strategy team regarding her puerperium in a city in the interior of Maranhão. Methodology: This study is exploratory, with a quantitative-qualitative approach. Data collection took place in august 2021. Results: It was observed that there is a gap in the knowledge of the puerperal women regarding their puerperium by the health team as a whole, noting that the focus of health professionals is on the newborn, forgetting the woman in her biopsychosocial state. Conclusions: It is concluded that the relationship between the nursing professional and the puerpery women is based on three pillars, problem-solutive capacity, aptitude for teaching and humanized contact, which are fundamental for better health promotion and prevention.